Multiple myeloma in Brazil: an assessment of Global Burden Disease study 2019 - Moura de Oliveira , Max; Veloso, Guilherme Augusto; Deborah Carvalho Malta, Deborah; Curado, Maria Paula; Menezes de Pádua, Cristiane (Saúde em Debate, 2024)
Multiple myeloma is the second most common hematological cancer; it accounts for approximately 10% of all hematologic malignancies and 1%-2% of all cancer diagnoses. From 1990 to 2019, an ecological study was conducted to describe and evaluate trends in Brazil’s morbidity, mortality, and disease. The Global Burden of Disease data described age-standardized (+40 years) incidence, prevalence, mortality, disability-adjusted life years, and its components in Brazil and across its 27 federative units according to sex and Socio-demographic Index quintiles. Trends were estimated using linear regression and expressed as Average Annual Percentage Changes (AAPC) and 95% Confidence Intervals (CI). Ascending trends of the measures were found for both sexes in Brazil and its federative units. Mortality increased to a lesser extent than incidence (AAPC=1.3%; 95%CI=1.2-1.3 vs. AAPC=1.5%; 95%CI= 1.5-1.5 for men; AAPC=0.9%; 95%CI=0.9-0.9 vs. AAPC=1.1%; 95%CI=1.1-1.2 for women), resulting in higher rising trends in prevalence for both sexes. All the measures were significantly higher in high- and high-middle socio-demographic quintiles; however, higher ascending trends were found in lower socio-demographic quintiles. Aging, level of development, diagnosis, and treatment appear to explain Brazil’s ascending multiple myeloma rates and their differences among the federative units.